PENGARUH BIAYA PRODUKSI TERHADAP HARGA JUAL PT.SIMPATINDO MULTI MEDIA BANYUASIN - Ernawati Ernawati (Jurnal RATRI (Riset Akuntansi Tridinanti), 2021)
The company PT.Simpatindo Multi Media Banyuasin is a company engaged in the field of trade and telecommunications as the National Authorized Dealer of Telkomsel where they provide services in the form of Telkomsel products both Mkios pulse providers and also various Telkomsel starter cards that are allocated from branch offices to sub branches office and will be marketed through salesmen.In achieving the sales target the company incurs costs, namely production costs, with high costs expected to get maximum results. Then the problem to be examined in this study is the extent of the effect of production costs on selling prices. Data collection techniques used are using financial statements. Data analysis technique used is quantitative descriptive method using simple linear regression analysis, proof of hypothesis by using t test and the coefficient of determination using SPSS 22.0 for windows.From the research results obtained by a simple regression equation can be seen that the cost of production has a large (positive) effect on the selling price. This can be shown from the regression equation Y = 6,872 + 1,050 which means that any increase in production costs will be followed by an increase in selling prices, whereas a decrease in production costs will also be followed by a decrease in selling prices. The effect of production costs on selling prices in this study is 99.8%, and the remaining 0.2% is influenced by other factors (variables) such as demand for product targets and competition in the market and consumer tastes. Based on research the company has recorded the costs well but needs to be considered in the calculation and recording in detail so that errors do not occur because costs have a large influence on the selling price. And it is expected that the company can maintain the quality and quantity of the product in the market so that it can provide good service to consumers.Keywords: Production Costs, Selling Prices